Gastroesophageal Reflex Disease among patients with Chronic Obstructive Pulmonary Disease in Saudi Arabia: A single center experience in Makkah - Alghamdi, Saeed Mardy; Alzahrani , Abdulaziz; Al Qarni, Omer; Alsaif , Sulaiman; Al Hindi, Abdulrahman; AlZaharani, Hassan; Al Hindi, Abdulghani; Alwafi, Hassan; Al Dhahir , Abdulelah; Alsulayyim, Abdullah; Alqahtani, Jaber; Alqarni, Abdullah; et al. (J Med Rehab Sci, 2025)
Background: This study aimed to investigate the prevalence of Gastroesophageal Reflux Disease (GERD) and its predictors among patients with Chronic Obstructive Pulmonary Disease (COPD) in Saudi Arabia. Methods: Analysis was conducted using electronic health records (EHR) of 706 adult COPD patients who visited outpatient pulmonary clinics between 1 August 2023, and 14 September 2024. GERD diagnosis was collected from EHR as well as endoscopic results, symptoms, and medication use. COPD was defined according to the Global Initiative for Chronic Obstructive Lung Disease (GOLD) criteria. Data on demographics, pulmonary function tests, comorbidities, and hospital admissions were collected. Statistical analyses included Chi-Square tests, Kruskal-Wallis tests, and binary logistic regression. Results: Among the 706 COPD patients, 186 (26.3%) had a diagnosis of GERD. The mean age of patients with GERD was 66.92 years, with equal gender distribution. Significant predictors of GERD included older age (OR: 1.60, 95% CI: 1.11-2.29), smoking (OR: 1.98, 95% CI: 1.37-2.87), presence of comorbidities (OR: 0.09, 95% CI: 0.04-0.17), and history of Acute Exacerbation of COPD (AECOPD) admissions in the previous year (OR: 0.35, 95% CI: 0.25-0.50). Conclusion: The study found that over a quarter of patients with COPD also had GERD. Key predictors of GERD in this patient population included older age, smoking, comorbidities, and recent AECOPD admissions. These findings highlight the importance of monitoring and managing GERD in patients with COPD to improve clinical outcomes.